2-methoxyestradiol inhibits melanoma cell growth by activating adaptive immunity. (4th July 2022) - Hua, Weitian; Huang, Xingfeng; Li, Jingyu; Feng, Wei; Sun, Yi; Guo, Chengrui
Abstract: Background: The overall survival of melanoma patients remains poor despite advancements in surgical treatment and targeted therapies. Therefore, there is a need to develop new therapeutic strategies for melanoma. 2-methoxyestradiol (2-ME) is a major metabolite of estrogen that has been shown to have anti-tumor effects against many malignancies. However, the effects and mechanisms of action of 2-ME against melanoma remain unclear. Materials and methods: Melanoma cells (B16) were treated with 2-ME in vitro. Cell proliferation was detected by CCK8 and clone formation, transwell was carried out to measure the migration of B16 cells with or without 2-ME. Flow cytometry was performed to measure the apoptosis and cell cycle. C57BL/6 mice were used for tumor-bearing of B16 cells, tumor volumes were measured once a day, and sacrificed after it was over 2000 mm3, then immunofluorescence was implemented to examine the marker of CD3, CD8 and PD-L1. Results: In our study, we found that 2-ME significantly affected the proliferation, migration, apoptosis, and cell cycle of melanoma in vitro. Our results also showed that 2-ME had strong anti-tumor effects against melanoma in vivo and increased the infiltration of tumor-specific cytotoxic lymphocytes CD8+ T cells in the tumor microenvironment. Besides, PD-L1 expression in tumor cells was significantly higher in the 2-ME-treated group than in the control group, indicating that 2-ME could exhibit stronger anti-tumor effects against melanoma if combined with PD-1 blockade therapy. Conclusion: 2-ME suppresses melanoma in vivo and in vitro and is a promising synergistic enhancer of PD-1 blockade immunotherapy.